Pharmacokinetic Interaction of Favipiravir with Citalopram and Pioglitazone - Zeliha Keskin ​ Alkaç; Dilan Aşkın Özek; Hande Yüce; Fatih Ahmet Korkak; Sümeyye Aslan; Neşe Başak Türkmen; Songül Ünüvar (Journal of Pharmaceutical Research, 2022)
The current study's objective was to investigate the interactions of favipiravir with pioglitazone and citalopram. 25 Spraque-Dawley female rats were used in the study. Rats in groups 1 and 4 were given pioglitazone (1 mg/kg/day) for 7 days and rats in groups 2 and 5 were given citalopram (1.5 mg/kg/day) for 7 days. Rats in groups 3, 4, and 5 were given a loading dose (50 mg/kg) on the 6th day of the study and a maintenance dose of favipiravir (30 mg/kg) on the 7th day of the study. After the last drug administration, blood samples were taken from the rats at 15, 30, and 45 minutes, and 1, 2, 4, 6, and 8 hours. Plasma concentrations of drugs were determined by high-performance liquid chromatography (HPLC). The aldehyde oxidase (AO) and xanthine oxidase (XO) activities in liver tissues were determined by enzyme-linked immunosorbent assay (ELISA). Pioglitazone changed the pharmacokinetics of favipiravir and increased t1/2, AUC, MRT and Cl values. Favipiravir did not affect the pharmacokinetics of pioglitazone at a steady state. When used together, favipiravir significantly decreased Cl while increasing citalopram's t1/2, AUC, and MRT values. While citalopram increased the t1/2, Cmax, AUMC, and Cl values of favipiravir, it decreasing the AUC value. Pharmacokinetic drug interactions have been determined between favipiravir and AO substrates or modulators. It is thought that if the results obtained are supported by human studies, it will guide the concomitant use of these drugs in the clinic to prevent the occurrence of adverse reactions. Keywords: Drug-drug interaction, Favipiravir, Pioglitazone, Citalopram, Aldehyde oxidase